BE_ZIVILSTRAF BK 2023 134 vom 23. Juni 2023 - BE Obergericht (2023)
classement / non-entrée en matière, procédure pénale pour abus d'autorité, evt. lésions corporelles simples | Einstellung/Nichtanhandnahme